IMPLEMENTASI LAGU “SENTUHAH BOLEH” SEBAGAI MEDIA EDUKASI DALAM PENCEGAHAN PELECEHAN SEKSUAL PADA ANAK DI TK BUDI MULIA KECAMATAN DAHA UTARA KANDANGAN - Asiah; Salhah; Yuliani (IAI DARUL ULUM KANDANGAN, 2024)
Early age is a potential period for learning for children. Various knowledge can be taught from an early age, one of which is about sex education and prevention efforts. It is very important to convey an understanding of sexual prevention to children, so that children can know what body parts other people can and cannot touch. The singing method is one method that children really like and enjoy. The song